Deficit Irrigation-Nutrient Coupling on Growth, Yield, Fruit Quality and Water Use Efficiency of Indian Jujube - Pal, Payel; Bam, Nyape; Patra, Sanmay Kumar; Ray, Ratneswar (International Journal of Bio-resource and Stress Management, 2021)
Sustainability of quality fruit production in Indian jujube is adversely affected by improper irrigation and nutrient management. A field study comprising of four irrigation levels (drip irrigation at 0.8, 0.6 and 0.4 of pan evaporation (E0) and surface irrigation at 1.0 IW/CPE with 50 mm depth) and three nutrient levels (100% RDF, 75% RDF+25% RDF as vermicompost and 50% RDF+50% RDF as vermicompost) was conducted during 2018-19 (11 months) on jujube plant. Results showed that tallest tree (3.72 m), greatest tree circumference (0.32 m), maximum fruits tree-1 (563), highest fruit weight (15.5 g) and fruit yield tree-1 (8.42 kg) were recorded with drip irrigation at 0.8 E0 with 100% RDF. Minimum growth, yield components and yield were found with drip irrigation at 0.4 E0 with 50% RDF+50% RDF as vermicompost. Seasonal ETa was 373.6, 409.4 and 446.4 mm for drip irrigation at 0.4, 0.6 and 0.8 E0, respectively and 694 mm for surface irrigation. Maximum CWUE of 18.87 g tree-1 mm-1 was obtained with drip irrigation at 0.8 E0 with 100% RDF. About 55.7-75.5% water was saved by drip irrigations which could bring an additional area of 55.5-85.8% under drip irrigated jujube. Highest predicted yield of 9.02 kg tree-1 was accomplished with 278 mm irrigation water. This model approach could serve as a good guideline to yield potential decision in relation to limited irrigation water for jujube growers in the Indo-Gangetic plains or similar agro-climatic regions.